Characteristics of postmortem organ donors in N.V. Sklifosovsky Research Institute for Emergency Medicine and the donor hospitals of FMBA of Russia (2008–2017) - V. L. Vinogradov; M. Sh. Khubutiya; K. K. Gubarev; V. G. Dulub; A. I. Zakhlevnyy; D. S. Svetlakova; S. E. Voskanyan; A. S. Samoylov (Трансплантология (Москва))
Rationale. There have been only single studies conducted in the Russian Federation to characterize the posthumous donor population.Objective: Identifying the main characteristics of the donor pool in N.V. Sklifosovsky Research Institute for Emergency Medicine of Moscow Healthcare Department and in the State Research Center – A.I. Burnasyan Federal Medical Biophysical Center, FMBA, for the period from 2008–2017.Material and methods. The clinical records of 429 actual and effective posthumous donors were analyzed retrospectively. The following characteristics were studied: gender, age, permanent place of residence, cause of death, the duration of mechanical lung ventilation, type of donation, total number of harvested organs, and number of organs recovered per donor.Results. There were 281 male and 148 female donors. The increase in the mean age of donors from 37 to 48.5 years was noted. Cerebrovascular disease and traumatic brain injury became the main causes of death. Since 2012, the rate of cerebrovascular diseases as the cause of donor death has increased from 30% to 70%. Of 429 actual donors, the brain death was diagnosed in 366 (85.3%). Four hundred eight deceased became effective donors. A total of 1,247 donor organs (744 kidneys, 220 livers, 42 pancreas, 2 intestines, 180 hearts, 58 lungs, and 1 facial vascularized composite allograft) were obtained. The mean number of donor organs recovered per donor was 3.06.Conclusions. The results obtained can be used to develop unified protocols and results of posthumous donors and to assess the possible volume of transplant care. In the period 2008–2017 an increase in the average age of posthumous donors (from 38.1 to 48.7 years) due to the proportion of donors in the 18–29 age group (from 29 to 4%) and an increase in the proportion of donors in the age group over 60 (from 3 to 15%). From 2012 to 2017 (from 68 to 29%) due to an increase in the number of donors who died as a result of cerebrovascular diseases (from 30 to 71%). Among the posthumous donors delivered by ambulance teams directly to the intensive care units, 69% of the consciousness level was depressed to 5 and lower on the Glasgow coma scale.